Comparison of Two Ginkgo biloba L. Extracts on Oxidative Stress and Inflammation Markers in Human Endothelial Cells. (25th June 2019) - Piazza, Stefano; Pacchetti, Barbara; Fumagalli, Marco; Bonacina, Fabrizia; Dell'Agli, Mario; Sangiovanni, Enrico
Abstract : Atherosclerosis is characterized by interaction between immune and vascular endothelial cells which is mediated by adhesion molecules occurring on the surface of the vascular endothelium leading to massive release of proinflammatory mediators. Ginkgo biloba L . (Ginkgoaceae) standardized extracts showing beneficial effects are commonly prepared by solvent extraction, and acetone is used according to the European Pharmacopoeia recommendations; the well-known Ginkgo biloba acetone extract EGb761® is the most clinically investigated. However, in some countries, the allowed amount of solvent is limited to ethanol, thus implying that the usage of a standardized Ginkgo biloba ethanol extract may be preferred in all those cases, such as for food supplements. The present paper investigates if ethanol and acetone extracts, with comparable standardization, may be considered comparable in terms of biological activity, focusing on the radical scavenging and anti-inflammatory activities. Both the extracts showed high inhibition of TNF α -induced VCAM-1 release (41.1-43.9 μ g/mL), which was partly due to the NF- κ B pathway impairment. Besides ROS decrease, cAMP increase following treatment with ginkgo extracts was addressed and proposed as further molecular mechanism responsible for the inhibition of endothelial E-selectin. No statistical difference was observed between the extracts. The present study demonstrates for the first time that ethanol and acetone extracts show comparable biological activities in human endothelial cell, thus providing new insights into the usage of ethanol extracts in those countries where restrictions in amount of acetone are present.